Research of the impact of the methods of extragent preparation on physical and chemical properties of exhausted beat slices - S. O. Semenikhin; N. M. Daisheva; N. I. Kotlyarevskaya; M. M. Usmanov (Новые технологии, 2019)
From the point of view of ensuring the stability of the mode of its conduct, the process of diffusion desugarization of beet slices, is largely determined by physical and chemical properties of beet slices, which are usually not controlled by production laboratories of enterprises. The article considers the main criteria necessary to achieve high physical and chemical properties of beet slices, which help to maintain the optimal hydrodynamic regime in a diffusion apparatus. A method is described for conducting laboratory studies of the amount of deformation, which indirectly characterizes the elastic modulus of sugar-free beet slices, with the three most widely used methods for preparing the extragent, namely sulfitation, acidification with sulfuric acid and addition of a gypsum slurry. Graphic dependences of the magnitude of the deformation by compression over time at various values of the generated pressure are given. The characteristic of the methods of extragent preparation is given from the point of view of their influence on physical and chemical properties of sugar-free beet slices. It has been established that the three most widely used in the industry methods of extragent preparing do not adversely affect the diffusion process, however, the sulfation of the extragent contributes to a greater deformation capacity of sugar-free beet slices - by 6.3% (of relative), therefore its subsequent pressing will be more effective compared to other methods of extragent preparation.